ANALISIS KELEMBAGAAN PASAR INPUT DAN OUTPUT USAHA TERNAK RAKYAT - RACHMAT HENDAYANA; FRITS WALLY (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
This study aims to investigate the characteristic of input and output market institutionsfor smallholder livestock and also identify factors influencing the market institutionperformance in smallholder livestock. Data are collected through unstructured interview usingParticipatory Rural Appraisal (PRA) with focus group discussion at Nabire in FY 2003covering 30 selected livestock farmers and some traders as interviewed respondent. Dataanalysis conducted using qualitative and quantitative description, and research result revealsthat: (a) input – output market institutions have important role as determinant factors insmallholder livestock especially the correlation of livestock farmer earnings, (b) Bargainingposition of farmer very weak in marketing of livestock output, because the market structure oftending to oligopoly, (c) Performance of livestock market not only influenced by internalfactor, however is also determined factor of external, (d) Motivation for form of mutualprofiting partner between livestock farmer and other party is needed to improve performanceof input-output marketing of livestock. .